2021
DOI: 10.3389/fmed.2021.792233
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiological Characteristics of Streptococcus suis Infections in Catalonia, Spain

Abstract: Introduction:Streptococcus suis (S. suis) is a human zoonotic pathogen of occupational origin, with infection acquired through contact with live pigs or pig meat. Pig farming is one of Catalonia's biggest industries and as a result this region of Spain has one of the highest density pig populations per km2. The aim of our study was to describe the infections caused by S. suis occurring in that area over a 9-year period.Materials and Methods: A retrospective, multi-center study was carried out by searching reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Studies of the prevalence of S. suis on pig farms in the three main European pig producing countries of Germany, the Netherlands and Spain showed 3.3 to 4.0% of pigs in infected farms had S. suis related disease with mortality rates of 0.5 to 0.9% [32] . In Spain, researchers found that 55.6% of patients worked in pig farms [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the prevalence of S. suis on pig farms in the three main European pig producing countries of Germany, the Netherlands and Spain showed 3.3 to 4.0% of pigs in infected farms had S. suis related disease with mortality rates of 0.5 to 0.9% [32] . In Spain, researchers found that 55.6% of patients worked in pig farms [31] .…”
Section: Discussionmentioning
confidence: 99%
“…All patients were male, with an average age of 48 ± 8.9 years, and more than half of them worked on pig farms. [ 2 ] In addition, 1 study found that once patients who had undergone splenectomy were infected with S suis , their immune system could not rapidly recognize and remove the pathogen owing to impaired immune function. Pathogens accumulates in the body and rapidly destroys tissues, resulting in hypertonic capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…[8] The most common clinical manifestation of S suis infection is meningitis, followed by septic arthritis, and approximately half of patients have residual hearing impairment. [2] For the anti-infection regimen of S suis infection, β-lactam antibiotics are used empirically to treat S suis infections and have been shown to be safe and efficacious. [17] However, for bacterial meningitis without knowledge of the causative pathogen, many guidelines recommend vancomycin plus β-lactam antibiotics.…”
Section: Datementioning
confidence: 99%
See 2 more Smart Citations